Functions of the Plant Qbc SNARE SNAP25 in Cytokinesis and Biotic and Abiotic Stress Responses - Won, Kang-Hee (Mol Cells, 2020)
Eukaryotes transport biomolecules between intracellular organelles and between cells and the environment via vesicle trafficking. Soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNARE proteins) play pivotal roles in vesicle and membrane trafficking. These proteins are categorized as Qa, Qb, Qc, and R SNAREs and form a complex that induces vesicle fusion for targeting of vesicle cargos. As the core components of the SNARE complex, the SNAP25 Qbc SNAREs perform various functions related to cellular homeostasis. The Arabidopsis thaliana SNAP25 homolog AtSNAP33 interacts with Qa and R SNAREs and plays a key role in cytokinesis and in triggering innate immune responses. However, other Arabidopsis SNAP25 homologs, such as AtSNAP29 and AtSNAP30, are not well studied; this includes their localization, interactions, structures, and functions. Here, we discuss three biological functions of plant SNAP25 orthologs in the context of AtSNAP33 and highlight recent findings on SNAP25 orthologs in various plants. We propose future directions for determining the roles of the less well-characterized AtSNAP29 and AtSNAP30 proteins.